PROTOCOL: When and how to replicate systematic reviews. Issue 2 (28th May 2020) - Karunananthan, Sathya; Maxwell, Lara J.; Welch, Vivian; Petkovic, Jennifer; Pardo, Jordi Pardo; Rader, Tamara; Avey, Marc T.; Baptiste‐Ngobi, John; Batista, Ricardo; Curran, Janet A.; Ghogomu, Elizabeth Tanjong; Graham, Ian D.; et al.
Abstract: This is a protocol for a co‐registered Cochrane and Campbell Review (Methodology). The objectives are as follows: To identify, describe and assess methods for: when to replicate a systematic review; how to replicate a systematic review.